2011
DOI: 10.1021/jp111501d
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of Capped Hexaglycine Strands into Hydrogen-Bonding Motifs Representative of Pleated and Rippled β-Sheets, Collagen, and Polyglycine I and II Crystal Structures. A Density Functional Theory Study

Abstract: We compare the energies and enthalpies of interaction of three and seven stranded capped polyglycine aggregates in both the pleated and rippled antiparallel and parallel β-sheet structures as well as the collagenic (3-strand) or polyglycine II-like (7-strand) forms using DFT theory at the B3LYP/D95(d,p) level. We present the overall interaction energies as broken down into pure Hbonding between the strands at the geometries they assume in the aggregates and the distortion energies required to achieve those geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 38 publications
(87 reference statements)
3
25
0
Order By: Relevance
“…4,9,40,41 Comparison of VQIVYK with VQIINK reveals that the interaction enthalpy for the strands at the edge of the sheet (1–2) reach a similar asymptotic value for both structures. However, the interactions nearer the center of the sheets are much stronger for VQIINK.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4,9,40,41 Comparison of VQIVYK with VQIINK reveals that the interaction enthalpy for the strands at the edge of the sheet (1–2) reach a similar asymptotic value for both structures. However, the interactions nearer the center of the sheets are much stronger for VQIINK.…”
Section: Resultsmentioning
confidence: 99%
“…9 We define the H-bonding energies as the interactions between the strands in the geometries of the optimized sheet, and the distortion energies as the energy required to change the geometry of the completely relaxed extended strand to that it assumes in the optimized sheet. This procedure has the advantage of allowing different conformations of the individual strands to be considered as starting points.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,35 Hence, we would expect AP interaction between the sheet and the cap to probably enhance the affinity of the cap for the sheet.…”
Section: Discussionmentioning
confidence: 99%
“…[ 41, 45–47 ] We have recently shown that B3LYP/D95(d,p) is among the better functional/basis set combinations for the water dimer. [ 48 ] We have used this level of calculation to calculate the differential enthalpies of adding successive alanines to a growing α‐helix, [ 49 ] the magnitudes of 13 C‐ 15 N 3 J‐trans H‐bonding scalar coupling constants, [ 50 ] the structures of polyglycine models, [ 51 ] and the H‐bonding interactions of the DNA base pairs. [ 52 ] Comparisons with experimental confirm the validity of the method in several cases.…”
Section: Calculational Detailsmentioning
confidence: 99%